Effect of Y2O3 addition on microstructure and mechanical properties of spark plasma sintered AlMgB14 and AlMgB14-TiB2. Issue 7 (May 2018) - Zhou, Y.M.; Zhang, T.; Xu, K.; Zhang, F.L.; Bai, K.; Huang, H.P.; Wu, S.H.; Luo, S.M.
Abstract: Owing to great hardness and low friction coefficients on steel, AlMgB14 has several potential applications in the fields of cutting tools and wear-resistant materials. In the current work, the effect of Y2 O3 addition on the mechanical properties and microstructure of spark plasma sintered AlMgB14 and AlMgB14 -TiB2 has been investigated. An increase in the amount of Y2 O3 led to an increase in the number of secondary phases including MgAl2 O4 and Y2 O3 in AlMgB14 matrix. The addition of Y2 O3 led to a refinement in the grain size of AlMgB14 and AlMgB14 -TiB2 ; however, simultaneously increased the porosity. With the addition of 3 wt% Y2 O3, both AlMgB14 and AlMgB14 -TiB2 reached the finest grain size and the highest hardness while maintaining a low porosity.